Improvement of the surface properties of polystyrene sheetsvia UV curable organic-inorganic hybrid coatings - DEMİRER, HALİL; KARTAL, İLYAS; ÇAKIR, MUSTAFA (My University, 2016)
This study describes the synthesis of silane terminated urethane, aimed at adding into epoxy acrylate, for the coating purposes. For this aim, firstly, silane terminated urethane was synthesized by the reaction between poly(hexamethylene carbonate) diol and 3-isocyanatopropyltrimethoxysilane. Pre-hydrolyzed TEOS and MEMO mixture was added to the silane terminated urethane. This solution was then mixed with organic part (epoxy acrylate and HDDA) to obtain hybrid solutions. Different organic-inorganic hybrid formulations were applied on polystyrene sheet surfaces by using applicators. The performance of the coatings on polystyrene sheets was investigated by applying physical and chemical tests. The results have shown that physical and chemical properties of polystyrene sheet surfaces were significantly improved.